Pakikipagkapwa-tao as a mode of inter-religious dialogue in the contemporary Philippines during the COVID-19 pandemic - Castillo, Fides A. del ca. 20./21. Jh. (HTS teologiese studies, 2023)
The study brought to the fore the issue of acute hunger and food insecurity in Philippine society during the COVID-19 pandemic. It utilised Filipino culture and the Catholic Church’s fidei depositum as a framework to unravel the forms of inter-religious dialogue in the country. The study was qualitative research that used a case study as it analysed inter-religious dialogue, particularly the dialogue of life and action among Filipinos during the coronavirus disease 2019 pandemic. In the Philippine context, dialogue takes the form of a shared life and common action. Also, the Filipino ideal of pakikipagkapwa-tao [having positive and sincere relations with one’s brethren] promotes positive inter-religious relations and social cohesion. The author argued that although religion compelled many believers to help the needy, it is pakikipagkapwa-tao that undergirds the care and concern of many Filipinos to those who are suffering. Pakikipagkapwa-tao enabled cordial cooperation between religious institutions and individuals, which promoted the physical well-being of the poor.Contribution: This study contributed to a deeper understanding of interfaith dialogue and relations in the contemporary Philippines.